Fictive motion in the context of mountaineering. Issue 4 (2nd October 2018) - Egorova, Ekaterina; Tenbrink, Thora; Purves, Ross S
ABSTRACT: Fictive motion in language (as in "the ridge went north") is claimed to reflect the attention focus of the observer on the extension and spatial layout of an entity. This paper investigates fictive motion in alpine narratives, which describe the experience of moving in a very specifically structured space. We examine space properties that are highlighted through fictive motion in this specific context and describe how they go beyond spatial extension. We further report the communicative motivation behind the use of fictive motion, ranging from conveying the sense of place to encoding the full spatial footprint of a motion event.